Integrating computational and experimental methods for efficient biocatalytic synthesis of polyesters - Alessandro Pellis; Lucia Gardossi (2019)
The research on biocatalyzed polycondensation has delivered an array of polyesters having molecular weights below 20,000 g mol− 1 but characterized by controlled structures and desired functionalities. Their unique catalytic efficiency under mild conditions enables enzymes to catalyze the polycondensation of monomers bearing labile lateral moieties that can be easily accessed via post-polymerization modifications. Despite this great potential, nowadays biocatalysts are not employed for polycondensation on industrial scale due to some bottlenecks related to the formulation of biocatalysts and the process configuration, which make the enzymatic technology non-economic. Recycling the enzymatic catalysts is not only a matter of producing an active and robust formulation, but it also requires the optimal integration of such biocatalyst within a specific reactor and process configuration that must enable efficient mass-transfer while preserving the integrity of the enzymatic preparation. In this chapter, we describe examples of integrated experimental-computational approaches for the rational planning and implementation of enzymatic polycondensation using lipase B from Candida antarctica and cutinase 1 from Thermobifida cellulosilytica. They rely on molecular visualization, molecular modeling and chemometrics, which are methods requiring very modest computational power and approachable by operators who do not have specific computational background. The examples also address the sustainability issue, by describing solvent-free processes involving bio-based monomers and biocatalysts immobilized on renewable carriers.